Review on combustion control of marine engine by fuzzy logic control concerning the air to fuel ratio - Koto, Jaswar (Penerbit UTM Press, 2014)
This research reviews a close loop control-oriented model, combined with air to fuel ratio, to regulate combustion phasing in a spark- ignition marine engine operation. On the other hand,Stoichiometric air-to-fuel ratio (λ) control plays a significant role on the three way catalysts in the reduction of exhaust pollutants of the SI marine engine. Air to fuel management for SI marine engines is a major challenge from the control point of view because of the highly nonlinear behavior of this system. For this reason, linear control techniques are unable to provide the required performance, and nonlinear controllers are used instead. Therefore, a fuzzy MIMO Control system is designed for robust control of lambda. As an accurate and control oriented model, an air to fuel ratio model of a Spark Ignition (SI) marine engine is developed to generate simulation data of the engine's subsystems. The Goal of this control is to maintain the A/F ratio at stoichiometry.